Regulatory obstacles to venture capital fundraising: a comparative study of Ukraine, the EU and the USA - Khort, J. V.; Хорт, Ю. В. (Одеса : Юрид. л-ра, 2014)
Legal assessment of regulatory obstacles to institutional allocations to Ukrainian venture funds is given in this article. The author suggests their significant liberalization, aiming inflow of capital to venture funds. Herewith, supervision of such investments by the authorized governmental agencies should be provided.
Khort J. V. Regulatory obstacles to venture capital fundraising: a comparative study of Ukraine, the EU and the USA / J. V. Khort // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 111-122.
Keywords: venture fund; venture capital; private equity fund; fundraising; collective investment institutions; венчурний фонд; венчурний капітал; фонд прямих інвестицій; інститут спільного інвестування; венчурный фонд; венчурный капитал; фонд прямых инвестиций; фандрейзинг; институт совместного инвестирования